Image distinguish CAPTCHA / Aimi Sakinah Mohamed - Mohamed, Aimi Sakinah (2007)
Image recognition CAPTCHA is not a new technology in the internet world. It also has the same objective as text recognition CAPTCHA which is to determine whether the user of the application is a bots or humans. In this paper, the researcher proposed a new type df image recognition CAPTCHA called image distinguish CAPTCHA that justrite a single click to pass the test. Through this study also, the researcher identify the characteristic df image recognition CAPTCHA and the differences between image recognition CAPTCHA and text recognition CAPTCHA. The research scope of this study is that the CAPTCHA can be implemented in web applications that using PHP platform with ih6 objective to make the web fibre secure.